2001
DOI: 10.1111/j.1750-3639.2001.tb00381.x
|View full text |Cite
|
Sign up to set email alerts
|

Central Role of Microglia in Neonatal Excitotoxic Lesions of the Murine Periventricular White Matter

Abstract: Periventricular leukomalacia (PVL) is the main cause of neurologic handicap in pre-term infants. The understanding of cellular and molecular mechanisms leading to white matter damage is critical for development of innovative therapeutic strategies for PVL. The pathogenesis of PVL remains unclear but possibly involves glutamate excitotoxicity as an important molecular pathway. We previously described a neonatal mouse model of excitotoxic white matter lesion mimicking human PVL. In the present study, we used thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
144
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(152 citation statements)
references
References 58 publications
6
144
0
Order By: Relevance
“…Several lines of evidence point to a role for neuronal glutamate receptors in many neurological disorders in neonates and adults (5,8,(24)(25)(26)(27). Here, we documented down-regulation just after birth of the AMPA-receptor subunits 1, 2, and 4; of the kainate-receptor subunit 7; and of the metabotropic receptor subunits 1, 2, 3, 5, and 7 in hypoxic mouse pups but not in hypoxic rat pups.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Several lines of evidence point to a role for neuronal glutamate receptors in many neurological disorders in neonates and adults (5,8,(24)(25)(26)(27). Here, we documented down-regulation just after birth of the AMPA-receptor subunits 1, 2, and 4; of the kainate-receptor subunit 7; and of the metabotropic receptor subunits 1, 2, 3, 5, and 7 in hypoxic mouse pups but not in hypoxic rat pups.…”
Section: Discussionmentioning
confidence: 56%
“…Because excitotoxicity and genetic regulation of glutamatereceptor expression are known to have a key role in brain damage (8,14,17,18), we investigated whether glutamate-receptor expression was altered by hypoxia, and whether these alterations differed between rats and mice, potentially explaining the phenotypic differences noted between these 2 species. We assessed the expression of glutamate-receptor subtypes in rat and mouse at early, intermediate, and late stages of brain development.…”
Section: Glial Phenotype After Gestational Hypoxia Differs Between Mousementioning
confidence: 99%
See 1 more Smart Citation
“…In our model, a significant increase of ameboid microglia occurred between 24 and 72 hours postischemia, during the window of vulnerability to selective HI white matter injury, as compared to controls. In the P7 rat, microglia have been implicated in the pathophysiology of neonatal injuries with a transient increase in microglial antigens between 24 hours and 3-4 days post HI in P7 rats (McRae et al, 1995), and after excitotoxic lesions of the developing murine periventricular white matter (Tahraoui et al, 2001). Here, we demonstrated that i) early NG2-positive OLs matured into O4-positive OLs in the cingulum and were also present at the vicinity of the cyst, and ii) increased macrophage/microglia phagocytosed O4-positive OLs, suggesting that the presence of activated microglia interferes with the maturation of immature OLs leading to impaired remyelination.…”
Section: Discussionmentioning
confidence: 99%
“…The PVWM regions are the most frequent site of preterm white matter injuries, such as periventricular leukomalacia, punctate lesions, and diffuse excessive high signal intensity, which are evident on magnetic resonance imaging (MRI). Animal studies have highlighted the critical role played by microglia in periventricular leukomalacia (16), lipopolysaccharide-induced inflammation (17,18), neonatal hypoxic-ischemic encephalopathy (17,19), and germinal matrix hemorrhage/intraventricular hemorrhage (GMH/IVH) (20). Despite a decrease in its incidence with routine use of both antenatal steroids and artificial surfactant at delivery, GMH/IVH remains one of the major complications of very preterm birth and brain injury.…”
mentioning
confidence: 99%